DIALOJEK: INTERFAITH DAILY DIALOG OF CHRISTIAN-MUSLIM OJEK DRIVERS IN SEKO LUWU-UTARA - Alam, Jems (Institut Agama Kristen Negeri Toraja, 2025)
Abstract: This paper aims to show the interfaith daily dialog of Christian-Muslim ojek drivers in Seko, Luwu-Utara. The author emphasizes the importance of interfaith daily dialog as a common space to encounter differences and uphold brotherhood through daily dialog as a life text. The method used in this research is a qualitative approach as a research procedure that produces descriptive data in the form of written or spoken words from people or observable behavior. This research was conducted in July-August 2024 in Seko. Data collection procedures were carried out through observation and interviews in the field, data examination, coherent data analysis and conclusion drawing. In this research, the author uses the theory of inter-religious and social solidarity as a perspective to see the interrelationship between interfaith dialogue which is influenced by the solidarity created in the community. In the end, this article concludes based on the research findings that daily interfaith dialog takes place in their life experiences across extreme paths. Roads, stalls and people's homes become common spaces for interfaith and ethnic encounters that give birth to shared experiences and create brotherhood. The solid attitude among them is united by common interests and responsibilities. On the other hand, the relationship between ojek drivers and the community is united by different needs and functions as a way of survival. Abstrak: Tulisan ini bertujuan memperlihatkan dialog keseharian lintas agama tukang ojek Kristen-Muslim di Seko Luwu-Utara. Penulis menegaskan pentingnya dialog keseharian antar agama sebagai ruang bersama memperjumpakan perbedaan dan menjunjung persaudaraan melalui dialog keseharian sebagai teks kehidupan. Metode yang digunakan pada penelitian ini adalah pendekatan kualitatif yakni suatu prosedur penelitian yang menghasilkan data deskriptif berupa kata-kata tertulis atau lisan dari orang-orang terkait perilaku yang dapat diamati. Penelitian ini dilakukan bulan Juli-Agustus 2024 di Seko. Prosedur pengambilan data dilakukan melalui observasi dan interview di lapangan, pemeriksaan data, analis data yang koheren dan penarikan kesimpulan. Subjek penelitian ini ialah Tukang Ojek. Dalam penelitian ini penulis menggunakan teori inter-religious dan solidaritas sosial sebagai perspektif melihat keterkaitan antar dialog lintas iman yang dipengaruhi oleh solidaritas yang tercipta dalam masyarakat. Pada akhirnya artikel ini menyimpulkan berdasarkan temuan penelitian bahwa dialog keseharian lintas agama berlangsung dalam pengalaman hidup mereka melintasi jalur yang ekstrim. Jalan, warung dan rumah warga menjadi ruang bersama dalam perjumpaan lintas iman dan etnis yang melahirkan pengalaman bersama serta menciptakan persaudaraan. Sikap solid diantara mereka disatukan oleh kepentingan dan tanggung jawab bersama. Pada sisi yang lain relasi tukang ojek dan masyarakat dipersatukan oleh kebutuhan dan fungsi yang berbeda sebagai cara bertahan hidup.